(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This research examines how contemporary digital technologies contribute to the enhancement of English vocabulary teaching. As mobile applications, interactive platforms, multimedia resources, and online learning environments become increasingly prevalent, technology serves as a powerful means for improving vocabulary acquisition among learners. The incorporation of visual, auditory, and contextual materials aids in a more profound comprehension and retention of new vocabulary, while gamified applications like Quizlet, Memrise, and Kahoot boost student motivation and promote autonomy. Furthermore, technology enables access to authentic language input through resources such as videos, digital dictionaries, and online corpora, which allow learners to see how vocabulary is used in real-life communication.